Learning Curves in 3‐Dimensional Sonographic Follicle Monitoring During Controlled Ovarian Stimulation. (1st April 2014) - Rodriguez, Amelia; Guillén, Juan José; López, Maria Jesus; Vassena, Rita; Coll, Oriol; Vernaeve, Valerie
Abstract : Objectives: Three‐dimensional (3D) sonographically based automated volume calculation (SonoAVC; GE Healthcare, Zipf, Austria) is being introduced in folliculometry during ovarian stimulation; however, clear training assessments in this technique are lacking. The learning curve–cumulative summation (LC‐CUSUM) test provides a quantitative tool to determine when a trainee has learned a procedure. The aim of this prospective study was to assess 3D SonoAVC LC‐CUSUM curves in folliculometry. Methods: Analyses were performed on 98 oocyte donors by capturing the ovarian image in 3D and applying the 3D SonoAVC software during ovarian stimulation cycles. Each patient was scanned by an expert operator and by a trainee. Independent LC‐CUSUM tests for 4 follicular diameters tracked the competency of 3 trainees in 3D SonoAVC. Results: We found that the numbers of sonographic examinations required by the 3 trainees to identify the correct number of follicles of 10 mm or larger were 38, 32, and 28, respectively; for follicles of 14 mm or larger, they were 29, 28, and 28; for follicles of 18 mm or larger, they were 24, 19, and 27; and for follicles of 21 mm or larger, they were 29, 19, and 24. Conclusions: A variable number of procedures are needed to reach proficiency in 3D SonoAVC, even for trained 2‐dimensional sonographers. Assessment of learning curves should be implemented when incorporating 3D SonoAVC in reproduction units.